Calcium pyrophosphate crystal deposition in a cohort of 57 patients with Gitelman syndrome. (11th September 2021) - Chotard, Emilie; Blanchard, Anne; Ostertag, Agnès; Latourte, Augustin; Gailly, Gilles; Frochot, Vincent; Lioté, Frédéric; Bousson, Valérie; Richette, Pascal; Bardin, Thomas; Vargas-Poussou, Rosa; Ea, Hang Korng
Abstract: Objective: Gitelman syndrome (GS) is the most frequent salt-wasting genetic tubulopathy and a source of hypokalaemia and hypomagnesemia. Chondrocalcinosis (CC) is a frequent feature of GS. The aim of our study was to determine the prevalence, distribution patterns, clinical phenotypes and risk factors for CC in GS. Methods: This prospective study of a cohort of 57 patients with GS included a systematic screening for CC by peripheral joint radiography, cervical spine CT and joint US. The prevalence of cervical C1–C2 CC by CT was compared between 33 GS patients and sex- and age-matched controls. Clinical and biochemical features were analysed to identify factors associated with CC. Results: Mean (s .d .) age of patients was 46.5 (12.4) years, 66.7% were women and 93.0% carried SLC12A3 mutations. Mean serum magnesium level was 0.60 (0.30) mmol/l. CC was observed in 79% of patients, with the highest prevalence at the cervical spine (81.8%) followed by the knee (52.6%), wrist (50.9%), ankle (38.6%), TM joint (36.4%), shoulder (33.3%), hip (22.8%), elbow (14.0%) and sclerochoroid (12.1%). Prevalence of CC at the C1–C2 level was higher in the GS cohort than control group (72.7% vs 9.1%) (adjusted odds ratio 21.0, 95% CI 2.8, 156.1, P = 0.003). Independent factors associated with CC were low serum magnesium level and age. Conclusion: GS was associated with widespread CC, favoured by aging and hypomagnesemia. The C1–C2 level was the most affected site. Follow-up of this unique cohort will help understanding the clinical consequences of CC, especially the precise characterization of pyrophosphate arthropathy.